VALUES OF LOCAL WISDOM OF SUNDANESE PROVERB - Hendry Sugara (Journal of Indonesian Language Education and Literary, 2016)
Indonesia is a nation that has an indigenous, ethnic, and cultural. Every tribe has its indigenous and traditions that vary according to the culture. People and culture is a unity that can not be separated because culture is created by the community, so the community is the owner of the culture itself. Each oral tradition with cultural values which are mostly used in the present generations for the future that is prosperous and dignified, but it takes an expert to explore, interpret, and apply it with a good cultural value. Cultural values in question here is the noble values that exist in the oral tradition and that guide the community at that time. We must acknowledge that the first measurable value to guide the ancestors is not necessarily completely relevant to today's life, there may even be the contrary to the life of the present. Writing is a form to understand or explore the values of local wisdom contained in papatah Sundanese people. This proverb is usually delivered by people who are more experienced or older to those who still lack experience or young child. But now very rarely papatah is used in everyday life because the development of more advanced age and curbs traditions or culture so that if no certain cultural revitalization will be lost. In this paper, the method used is a method of hermeneutics. This method does not search for the true meaning, but the meaning is the most optimal.